2006
DOI: 10.1196/annals.1374.126
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Study of Rickettsioses among Acute Febrile Patients in Central Tunisia

Abstract: Although Mediterranean spotted or "boutonneuse" fever (MSF) has been documented in central Tunisia, other spotted fever group rickettsioses (SFGR) and typhus group rickettsioses (TGR) have received little attention in our region. We sought to determine the role of rickettsioses, Q fever, ehrlichioses, and bartonelloses among patients with acute fever. The results of this study of 47 persons with acute fever of undetermined origin are reported in this paper. We concluded that SFGR, murine typhus, and acute Q fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 12 publications
3
29
0
Order By: Relevance
“…Other countries in Africa have reported similar (28%–58%) seroprevalence ( 9 , 10 ). The finding that prevalence of IgG to SFG rickettsiae increased with age can, in part, be explained by cumulative exposure to the pathogen and lifelong persistence of IgG.…”
Section: Discussionmentioning
confidence: 60%
“…Other countries in Africa have reported similar (28%–58%) seroprevalence ( 9 , 10 ). The finding that prevalence of IgG to SFG rickettsiae increased with age can, in part, be explained by cumulative exposure to the pathogen and lifelong persistence of IgG.…”
Section: Discussionmentioning
confidence: 60%
“…Two studies of febrile patients in Sousse, Tunisia, serologically identified acute Q fever in 2% and 9% of hospital admissions [54], [55]. Q fever was responsible for 5% of patients with acute febrile illness hospitalized in Bobo-Dioulasso, Burkina Faso [56] as well as 3% of pediatric and 8% of adult admissions for severe febrile illness at two referral hospitals in the Kilimanjaro Region of northern Tanzania [11].…”
Section: Resultsmentioning
confidence: 99%
“…R. felis was first detected (as 'R. ctenocephali') in C. felis in Europe in 1918, (Parola et al, 2003;Kaabia et al, 2006;Znazen et al, 2006;Williams et al, 2011). More recently, a study conducted over 9 months in two Senegalese villages, found that up to 6% of 134 indigenous febrile non-malaria patients were infected with R. felis (Socolovschi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%